Classification of Non-Affine Non-Hecke Dynamical R-Matrices - Avan, J.; Billaud, B.; Rollet, G. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
A complete classification of non-affine dynamical quantum R-matrices obeying the Gln(C)-Gervais-Neveu-Felder equation is obtained without assuming either Hecke or weak Hecke conditions. More general dynamical dependences are observed. It is shown that any solution is built upon elementary blocks, which individually satisfy the weak Hecke condition.